PENGARUH KUALITAS LAYANAN DAN PENYEDIAAN FASILITAS TERHADAP KEPUASAN KONSUMEN DI ERA PANDEMI COVID19 (Studi Kasus Penumpang KA PT KAI (Persero)) - Ananta Prathama; Ayunda Nabila Mauliddia; Daniar Seri Firdausi (Journal Publicuho, 2021)
PT KAI (Persero) is a company engaged in transportation services. The development of transportation modes due to the changing times and the COVID19 pandemic have made transportation companies competing to maintain consumer satisfaction. This study aims to see the effect of service and service influence on customer satisfaction of PT KAI (Persero) train users in the era of the Covid19 pandemic. The sampling method in this study was purposive sampling with a total population of 60 respondents who used PT KAI's train service in the past year or during the COVID19 pandemic. The data used in this research are primary data and secondary data. Primary data is data taken from questionnaires, while secondary data is data that comes from books, journals or other literature. Data processing methods in this study consisted of editing, scoring, and tabulation. Data analysis technique used in this study was processed through SPSS software (Social Science Statistical Package) which consists of multiple linear regression equations, classical assumption test, multiple coefficients of determination (R2), F test and ttest. The test instrument used in this study is validity and reliability test.